Некоторые особенности магнитных цепочных наносистем; На стыке наук. Физико-химическая серия; Т. 1 - Зятьков Д. О. Денис Олегович; Юрченко В. И.; Балашов В. Б.; Юрченко А. В. Алексей Васильевич (2015, 2015)
Заглавие с экрана